ANALYSIS OF THE EFFECT OF TAX AVOIDANCE AND TAX RISK ON FIRM VALUE WITH INDEPENDENCE COMMISSIONERS AS A MODERATING VARIABLE IN BASIC AND CHEMICAL INDUSTRY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2018-2022 - Loist Villi Darmawan; Abdillah Arif Nasution; Sirojuzilam Hasyim (CV. Radja Publika, 2026)
This study aims to empirically examine and analyze the effect of tax avoidance and tax risk on firm value with independent commissioners as a moderating variable in basic and chemical industry companies listed on the Indonesia Stock Exchange during the period from 2018 to 2022, based on shareholder theory. This research was conducted using descriptive statistical methods with the assistance of Eviews 12, where the sampling technique employed purposive sampling. The panel data regression method was applied to test the hypothesis, while Moderated Regression Analysis (MRA) was used to determine whether the moderating variable strengthens or weakens the relationship between the independent variables and the dependent variable. A total of 35 companies were selected as the research sample. The result of the outlier test indicated that the remaining sample used in the analysis consisted of 122 observations. The results of the study indicate that the tax avoidance variable has a negative and significant effect on firm value. The tax risk variable has a negative but not significant effect on firm value. Independent commissioners are able to strengthen the negative effect of tax avoidance on firm value. However, independent commissioners are not able to significantly strengthen the negative effect of tax risk on firm value.